2020
DOI: 10.1007/s43440-020-00168-1
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of people infected with SARS-Cov-2, treated with amantadine

Abstract: Background We conducted an observational study of 15 patients from a Southeastern area of Mexico with symptoms compatible with SARS-Cov-2, which were treated with the antiviral amantadine. Methodology In this study, data were collected from 15 individuals with clinical symptoms of COVID-19 infection, which were treated on an ambulatory basis with 100 mg of amantadine for a period of 14 days. Results This drug demonstrated its effectiveness, as patients recovered successfully with this treatment without the nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Only three observational clinical case reports with small numbers of patients ( n ≤ 15 for all) speculated that amantadine may be used for COVID-19 treatment, no systematic clinical trial in a human population was performed. 47 49 Some other papers only raised a hypothesis but without any validation experiment. 50 , 51 In this study, we systematically investigated the role of amantadine in the treatment of COVID-19 and found that amantadine inhibited CTSL enzyme activity in the setting of SARS-CoV-2 pseudovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Only three observational clinical case reports with small numbers of patients ( n ≤ 15 for all) speculated that amantadine may be used for COVID-19 treatment, no systematic clinical trial in a human population was performed. 47 49 Some other papers only raised a hypothesis but without any validation experiment. 50 , 51 In this study, we systematically investigated the role of amantadine in the treatment of COVID-19 and found that amantadine inhibited CTSL enzyme activity in the setting of SARS-CoV-2 pseudovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…In 1976, amantadine was developed for the treatment of influenza H1N1; however, this drug is not recommended for the treatment of influenza, because it mutates and loses sensitivity to the drug [ 112 ]. A small observational study of amantadine in COVID-19 gave some promising results [ 112 ]. The potential utility of memantine and other adamantane derivatives in COVID-19 has been recently discussed.…”
Section: The Lessons From the Immunomodulatory Therapy Of Covid-19 Fomentioning
confidence: 99%
“…For instance, the drugs amantadine and rimantadine, formerly approved as anti-Influenza A virus agents, have gained attention as possible antiviral agents for other virus-driven infections [ 14 ]. In this respect, an observational study described the amantadine as a possible repurposing drug for patients with Coronavirus disease 2019 (COVID-19) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%